The effect of oxygenates on the oligomerisation of propene over zeolite ZSM-5 - Langford, Steven Thomas (Department of Chemical Engineering, 2016)
The oligomerisation of alkenes such as propene and butene represents an important route to the production of environmentally clean transportation fuels. When these olefins originate from Fischer-Tropsch product streams they are often contaminated with small amounts of oxygenates such as acetic acid, ethanol, butanol, methyl-ethyl-ketone (MEK), acetone and water. Complex feeds can result in competitive reaction between the feed components and may result in observed selectivities that cannot be predicted from pure component data alone. ZSM-5 has been shown to be an excellent catalyst for alkene oligomerisation and is also active for the conversion of oxygenates. When pure oxygenates are fed over ZSM-5 at oligomerisation temperatures, acetone and MEK cause the catalyst to deactivate and the conversions are low whereas ethanol and n-butanol are completely converted and no deactivation occurs. At 250°C acetic acid undergoes a low conversion (4%) and at higher temperatures a decrease in conversion is also observed with time. The decrease in conversion of acetone has been attributed to the formation of a surface cyclic ketonic species. During acetic acid reaction dehydroxylation of the zeolite has been proposed as the cause of decreasing activity with time but this work has shown that the catalyst is regenerable and the acidity of the catalyst, as determined by ammonia TPD, remains unchanged after reaction with acetic acid. The propene oligomerisation and hexane cracking activity of ZSM-5 (Si/Al = 30) is reduced when the catalyst is exposed to oxygenates such as acetic acid, ethanol, n-butanol, MEK, acetone and water (mole fraction in feed < 0.01). In the case of all except acetic acid the activity is almost completely restored when the oxygenate is removed. Acetic acid causes irreversible loss of activity for propene oligomerisation and hexane cracking at 250°C. For MEK and acetone the activity for propene oligomerisation is restored to a greater extent (90% for acetone and 50-60% for MEK) than acetic acid but not fully. The decrease in activity for propene oligomerisation and hexane cracking at 250°C is proposed to be due to site poisoning by preferential strong adsorption of the oxygenates, especially acetic acid, onto the zeolite surface. An adsorption complex for acetic acid and the surface hydroxyls has been proposed in which the bond angles and lengths of the molecule are similar to those observed in the formation of the acetic acid dimer, consistent with the proposed strong adsorption.